Differences between reference intervals of blood counts of Brazilian adults with and without sickle cell trait according to laboratory tests from the National Health Survey - Ana Carolina Micheletti Gomide Nogueira de Sá; Alanna Gomes da Silva; Crizian Saar Gomes; Antonio Tolentino Nogueira de Sá; Deborah Carvalho Malta (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2023)
ABSTRACT Objective: To compare reference intervals (RI) of blood counts of Brazilian adults with and without sickle cell trait (SCT). Methods: Cross-sectional study, based on the National Health Survey, 2014-2015, composed of 8,952 individuals. The sample of patients with SCT was composed of 234 adults. The RIs of adults with and without SCT were compared in the study "Reference values for laboratory tests of blood count in the Brazilian adult population: National Health Survey", by Rosenfeld et al. (2019). The parametric method and the Student's t test were used for comparison (p≤0.05). Results: There were statistically significant differences between RIs of adults with and without SCT as far as sex is concerned for hemoglobin, MCV, MCH, MCHC, white blood cells, absolute lymphocytes, mean platelet volume and RDW; At all ages, for white blood cells and RDW in men and for MCV, MCH, MCHC, mean platelet volume and RDW in women; Between 18 to 59 years, for MCH, MCV, MCHC, neutrophils, lymphocytes and platelets in men and in women for lymphocytes, red blood cells, white blood cells, neutrophils, eosinophils, monocytes and platelets; From 60 years old on, for hemoglobin and hematocrit in men and in women for hematocrit, white blood cells, neutrophils and platelets; In white, black and brown people for white blood cells, neutrophils and platelets (p<0.05). Conclusion: Brazilian adults with SCT had lower counts of hemoglobin, MCV, MCH, MCHC, white blood cells and higher RDW than without SCT. The results show the importance of genetic counseling and further research to support the proper management of this condition in Brazil.